Analisis Pelaksanaan Program Pembatasan Kegiatan Masyarakat (PPKM) dalam Penanggulangan Pandemi Covid-19 Di Kota Banda Aceh Tahun 2021 - Imanullah, Ayu; Muklir, Muklir; Nirzalin, Nirzalin (Jurnal Transparansi Publik (JTP), 2023)
This study examines the policy implementation of the Community Activity Restriction Program (PPKM) in the city of Banda Aceh in tackling the COVID-19 pandemic. The PPKM policy is a serious effort by the government to overcome the problem of the COVID-19 pandemic. However, in its implementation in Banda Aceh, it was realized that the policy had a number of deficiencies, so the results intended to be achieved did not work effectively. Thus, this study aims to describe the process of implementing the PPKM policy in the city of Banda Aceh and why the implementation did not work as effectively as expected. The research method used in this research is the descriptive-qualitative method. The research results show that the process of implementing the PPKM policy in Banda Aceh City cannot be separated from the implementation of the four indicators of policy implementation put forward by George Edward III, namely: communication, resources, executor's attitude, and bureaucratic structure. As for the obstacles to the implementation of the PPKM policy in Banda Aceh City, the Banda Aceh City Government is not committed to determining the Task Force Team, which makes the community respond ambiguously, as well as the attitude of officers towards a number of people who are not cooperative, so that conflicts are prone to occur between the community and officers